IMPLEMENTATION OF THE ENTERPRISE RESOURCE PLANNING (ERP) SYSTEM ON MICRO, SMALL AND MEDIUM ENTERPRISES (MSME) BUSINESS ACTORS - Faranita, Widya Refri; Nugroho, Marno (Universitas Muhammadiyah Yogyakarta, 2021)
Several MSMEs in Indonesia have used a lot of Enterprise Resource Planning (ERP) systems in running their business to be able to maintain their business and be able to become market leaders. However, in this ERP system, there are several limitations for MSMEs, especially in the ability of human and financial resources. This study is divided into two parts, in the first part universal success indicators from the ERP success measurement literature will be tested using factor analysis. Data will be collected on 27 indicators of success through a structured questionnaire from end users of the ERP system. The results that will later be obtained are whether ERP is suitable to be implemented to meet the achievement of goals in managing a business run by MSMEs.